ERKIN KURASHCHI XOTIN-QIZLARNING MUSOBAQA OLDI TEXNIK TAYYORGARLIKNI RIVOJLANTIRUVCHI MASHQLAR MAJMUASINI RIVOJLANTIRISH - Primbetov, A.A. (SCIENCE and SOCIETY, 2023)
This article explores the meticulous development of a comprehensive set of exercises aimed at enhancing the pre-competition technical preparation of women freestyle wrestlers. The study delves into the unique physical and technical requirements of this dynamic sport, addressing the specific needs and challenges faced by female athletes. Drawing upon extensive research and expert insights, the exercises are meticulously designed to optimize the athletes' strength, agility, endurance, and tactical prowess, ensuring they are primed for success in the highly demanding world of freestyle wrestling. The article sheds light on the scientific principles and training methodologies underpinning the exercise regimen, providing a valuable resource for coaches, trainers, and athletes striving for excellence in women's freestyle wrestling.
Keywords: women's freestyle wrestling; pre-competition technical preparation; exercise development; female athletes; strength and agility training; wrestling tactics; training methodologies; wrestling performance optimization